NEWTON’S LAWS AND THEIR TEACHING IN HIGH SCHOOL: AN INVESTIGATIVE APPROACH - Moura, Tiago Martins; Moura, Cristiane de Carvalho Ferreira Lima; Silva, Maria Goretti; Celedonio, Natália Rocha; Ferreira, Lidiane Martins Moura (Seven Editora, 2025)
The persistence of traditional practices in Physics teaching, characterized by excessive mathematical formalism and a content-transmission-centered approach, still hinders students’ construction of meaning in secondary education. In the case of Newton’s Laws, such an approach tends to privilege the mechanical application of formulas to the detriment of conceptual understanding and the problematization of phenomena. This article aims to discuss theoretical and didactic foundations for teaching Newton’s Laws and to present an inquiry-based proposal aligned with the Brazilian National Common Curricular Base (BNCC), aimed at overcoming such formalism. This is a theoretical-bibliographic study grounded in constructivist frameworks and contributions from inquiry-based science education, articulating assumptions of the Science, Technology, Society and Environment (STSE) approach, elements from the History and Philosophy of Science (HPS), and the use of Digital Information and Communication Technologies (DICT). The proposal is structured around the investigation of contextualized problem situations that mobilize prior knowledge, teacher mediation for the formulation of students’ hypotheses, and the conceptual systematization of the three laws of motion. As potential outcomes, this proposal fosters an inquiry-based approach that promotes the construction of meaning regarding the relationships among force, mass, and motion, expanding evidence-based argumentation and strengthening students’ scientific autonomy. It is concluded that this teaching proposal contributes to overcoming formalism in the teaching of Newton’s Laws, requiring pedagogical intentionality, formative assessment, and teacher education consistent with current curricular guidelines.